Autoeficácia relacionada às quedas em idosos comunitários com dor lombar agudizada - Nayza Maciel de Britto Rosa (2012)
Population aging is a global phenomenon and specifically in Brazil, it occurs in an accelerated manner. In addition to this demographic transition, there is an epidemiological transition in which infectious diseases are replaced by chronic degenerative and its comorbidities. The Low Back Pain (LBP) is one of the most disabling pain conditions and therapeutically challenging that strikes the elderly, however, has been little studied. The concept of self-efficacy is important for the study of the falls, because it makes a connection between trust and performance in carrying out activities. Have high levels of self-efficacy in performing daily activities without falling is associated with better functional outcomes. The aim of this study was to investigate the association of clinical and functional factors with falls efficacy in the elderly with LBP acute. This is an observational cross-sectional with sample of one hundred twenty elderly ( 65 years) in the metropolitan region of Belo Horizonte. A structured questionnaire was drawn up with sociodemographic data, clinical and functional tests standardized for the elderly population. The falls efficacy was assessed by the scale Falls Efficacy Scale-International-Brazil (FES-I-BRAZIL). The association between clinical factors and functional with the falls efficacy was assessed by Multiple Linear Regression, Backward method, adopting a significance level of 5%. The average age of the elderly participants was 71.1 ± 5.4 years. The linear regression model that contained the explanatory variables age, scholarity, income, intensity of low back pain, self-perceived health, depressive symptoms, disability (verified by Roland Morris), falls (if it fell the previous six weeks and the number of falls), level of physical activity and gait speed was significant and showed that the independent variables explained 44.3% (R2 = 0.443, p <0.001) of change in falls efficacy. The method Backward has defined that the best model to explain the variation in falls efficacy was composed by the explanatory variables of LBP intensity, disability and scholarity. This model was significant and explained 42.4% (R2 = 0.424, p <0.001) of the dependent variable. This study provided an expanded view and depth about the falls efficacy in elderly with LBP, highlighting which intensity of low back pain, disability verified by Roland Morris and scholarity are the variables that more explained the falls efficacy in elderly with LBP. Identify what are the factors that explain and influence the self-efficacy has the potential to help the physiotherapist about the best way to evaluate and direct the exercises program of prevention or rehabilitation for the elderly with LBP who are at risk of falling.